Buginese Interference into Indonesian: Word Order Level - Balla, Arifuddin (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The goal of this study is to examine which word order is dominant in colloquial Buginese-Indonesian, 1) to find out which word-order pattern is more acceptable between SVO and VSO, 2) to find out which word-order pattern is more acceptable between VO and OV, and 3) to find out what internal linguistic characteristics and social factors motivate such acceptability. The data were collected through an online survey via Monkey Survey that employed Acceptability Judgment Task (AJT) to determine which word order is more acceptable in Buginese Indonesian (SVO or VSO and VO or OV). A total of 50 Buginese-Indonesian bilinguals rated the acceptability of 48 target items (and 48 fillers) for patterns such asÂ SVO/VSO and VO/OVÂ in a 1-5 Likert Scale (1=completely unnatural; 5=compeletely natural). Target items were controlled for linguistic factors and social factors. ANOVA analysis was used to analyze the data. The results indicate that both SVO and VSO are equally acceptable though VSO was slightly more favorable than SVO. When the subject is omitted, VO was farther favorable than OV. L1, age, and residence had a significant effect on the acceptability of VSO while grammatical person, education level, and residence contributed greatly to the acceptability of VO. The results also reveal that the acceptability of different word orders in Buginese-Indonesian is both linguistically and socially constrained. Thus, the results are situated within a discussion of Backus' (2014) notion of entrenchment and conventionalization.